Iron-Deficiency Anemia Results in Transcriptional and Metabolic Remodeling in the Heart Toward a Glycolytic Phenotype - Chung, Yu Jin; Swietach, Pawel; Curtis, M. Kate; Ball, Vicky; Robbins, Peter A.; Lakhal-Littleton, Samira (Frontiers in Cardiovascular Medicine, 2021)
Iron deficiency is the most prevalent micronutrient disorder globally. When severe, iron deficiency leads to anemia which can be deleterious to cardiac function. Given the central role of iron and oxygen in cardiac biology, multiple pathways are expected to be altered in iron-deficiency anemia, and identifying these requires an unbiased approach. To investigate these changes, gene expression and metabolism were studied in mice weaned onto an iron-deficient diet for 6 weeks. Whole-exome transcriptomics (RNAseq) identified over 1,500 differentially expressed genes (DEGs), of which 22% were upregulated and 78% were downregulated in the iron-deficient group, relative to control animals on an iron-adjusted diet. The major biological pathways affected were oxidative phosphorylation and pyruvate metabolism, as well as cardiac contraction and responses related to environmental stress. Cardiac metabolism was studied functionally using in vitro and in vivo methodologies. Spectrometric measurement of the activity of the four electron transport chain complexes in total cardiac lysates showed that the activities of Complexes I and IV were reduced in the hearts of iron-deficient animals. Pyruvate metabolism was assessed in vivo using hyperpolarized 13C magnetic resonance spectroscopy (MRS) of hyperpolarized pyruvate. Hearts from iron-deficient animals showed significantly decreased flux through pyruvate dehydrogenase and increased lactic acid production, consistent with tissue hypoxia and induction of genes coding for glycolytic enzymes and H+-monocarboxylate transport-4. Our results show that iron-deficiency anemia results in a metabolic remodeling towards a glycolytic, lactic acid-producing phenotype, a hallmark of hypoxia.